Informational nature of money - V. D. Kuligin (Вестник университета)
The study of the relationship between information and money is one of the most relevant, widely discussed and yet difficult issues to explore. However, many aspects remain unclear, requiring deeper research and understanding. The object of this study was the nature of subjective assessments, their qualitative and quantitative characteristics in  relation to the direct exchange of things. The content of objective exchange value as a relative value that is not measurable has been revealed in the article. It carries with it information about the proportion of things exchanged. The quantitative ratio of the value of the available monetary units and the units value of goods exchanged for them determines the price of money. The connection between commodity and credit money has been traced. It has been proved that money fulfills its information function as imaginary, ideal money. It has been concluded about the spontaneous adaptation of the competitive markets, money and prices information system to the conditions of falling purchasing power of money. The results of the study extend knowledge about the informational nature of money and outline perspectives for further research.